Health and nutritional status of school children from a rural area of Andhra Pradesh - G., Nanditha; Iyer, Chandrakala R.; A., Chandrashekar M.; Kancherla, Poojitha; Golluri, Raghuveer; ., Janakiraman (International Journal of Contemporary Pediatrics, 2020)
Background: Healthy children build a wealthy nation. Good health of children is of paramount importance to the nation’s growth. Health and nutritional status of school children is highly variable from one region to another due to different environmental, socioeconomic and cultural factors. Hence health status of school children from each area should be assessed periodically so that relevant health programmes can be applied to prevent common morbidities such as malnutrition, infections and infestations. Methods: A cross sectional study of 500 rural school children from 5 to 15 years was conducted to assess the nutritional status by anthropometry and health status by clinical examination. Results: Out of the 500 school children 46.8% girls, 71.4% were 5 to 10 years old, 70.2% studying in 1st to 5th class. 33.4% were stunted. 25.6% and 27% were underweight according to weight and Body mass index criteria respectively. Common health problems among school children in this study were anemia (31%), dental caries (27.2%), upper respiratory infections (13.4%), skin infections and scabies (12.6%), head lice infestation (6.8%), refractive errors (6%) and ear discharge (5.2%). Conclusions: Though the pattern of nutritional and health problems were same in different studies, the severity of them varied from region to region. Hence periodic screening of school children to identify them and to apply relevant health programmes goes a long way in reducing such morbidities.